Multilateral Trade Negotiations: Doha to Bali and Beyond - Fasih Uddin (Policy Perspectives, 2015)
The latest round of multilateral trade negotiation under the World Trade Organization (WTO) – known as the Doha Development Agenda – has remained inconclusive for well over 13 years. There have been serious differences between the developed and developing countries on issues such as market access and agricultural subsidies. While a compromise deal was reached in the Bali ministerial conference of the WTO, making the round a success remains an uphill task as divergences are there and apparently reaching a consensus is hard. However, it will be in the interest of all the member nations and the global economy to take the round towards a successful conclusion.